Hubungan Pengetahuan Terhadap Pemanfaatan Layanan Tes HIV pada Ibu Hamil Saat Kunjungan Antenatal Care di Puskesmas Sukasada I - Wigutomo Gozali; Putu Irma Pratiwi; Ni Nyoman Ayu Desy Sekarini; Anjar Tri Astuti (Indonesian Journal of Midwifery (IJM), 2022)
World Health Organization (WHO) offers cooperation towards zero new HIV infections among infants by 2020 and the elimination of hepatitis B and syphilis as a public health threat by 2030. Mother-to-child transmission (MTCT) is the most common way of acquiring HIV infection in children. children because more than 90% of new infections among children are through mother-to-child transmission. identify the relationship between knowledge and the use of HIV testing services for pregnant women during antenatal care visits at the Sukasada I Public Health Center. Methods: This study used a quantitative research design with a cross-sectional study design. This research was conducted in the working area of the Sukasada I Health Center and was conducted from May-June 2022. The sample in this study was 60 pregnant women who came to do a pregnancy check at the Sukasada I Health Center. The sampling technique in this study was accidental sampling. The test used in this study was the Chi Square test with P value <0.05. Results: Knowledge of pregnant women about HIV/AIDS is in the good category, as many as 29 people (48.33%). The use of HIV testing services for pregnant women showed that 35 people (58,33%). The results of statistical tests using chi square analysis, the value of p=.001 is smaller than the significance level of P value of 0.05. Conclusion: There is a Relationship between Knowledge and Utilization of HIV Testing Services for Pregnant Women During Antenatal Care Visits at Sukasada I Public Health Center. Abstrak Organisasi Kesehatan Dunia (WHO) menawarkan kerjasama menuju nol infeksi HIV baru di antara bayi pada tahun 2020 dan penghapusan hepatitis B dan sifilis sebagai ancaman Kesehatan masyarakat pada tahun 2030. Penularan dari ibu ke anak (MTCT) adalah cara paling umum untuk mendapatkan infeksi HIV pada anak karena lebih dari 90% infeksi baru diantara anak-anak adalah melalui penularan ibu ke anak. mengidentifikasi hubungan pengetahuan terhadap pemanfaatan layanan tes HIV pada ibu hamil saat kunjungan antenatal care di Puskesmas Sukasada I. Metode: Jenis penelitian ini menggunakan rancangan penelitian kuantitatif dengan desai penelitian cross sectional. Penelitian ini dilakukan di wilayah kerja Puskesmas Sukasada I dan dilakukan dari bulan Mei-Juni 2022. Sampel pada penelitian ini adalah ibu hamil yang datang untuk melakukan pemeriksaan kehamilan di Puskesmas Sukasada I sejumlah 60 orang. Teknik pengambilan sampel dalam penelitian ini adalah accidental sampling. Uji yang digunakan dalam penelitian ini adalah uji Chi Square dengan P value <0,05. Hasil: Pengetahuan ibu hamil mengenai HIV/AIDS berada pada kategori baik yaitu sebanyak 29 orang (48,33%). Pemanfaatan layanan tes HIV pada ibu hamil didapatkan hasil sudah memanfaatkan tes HIV/AIDS sebanyak 35 orang (58,33%). Hasil uji statistic menggunakan analisis chi square nilai p= .001 lebih kecil dari tingkat kemaknaan P value 0,05. Kesimpulan: Terdapat Hubungan Pengetahuan Terhadap Pemanfaatan Layanan Tes HIV pada Ibu Hamil Saat Kunjungan Antenatal Care di Puskesmas Sukasada I.